Microplastics contamination in the gills of Scylla spp. from the Selangor River Estuary, Malaysia - Ahmad Sabri, Nawaltul Akma; Mohamed, Nazarudin; Razak, Muhammad Raznisyafiq; Madzin, Zafira; Karim, Murni Marlina; Aris, Ahmad Zaharin (Elsevier, 2025)
Microplastics (MPs) pollution is a growing environmental concern owing to its widespread presence and risks to aquatic ecosystems. This study examined MPs in the gills of Scylla spp. from estuarine and coastal regions of Malaysia. As key mangrove species with high pollutant exposure, Scylla spp. serve as bioindicators of MPs contamination in brackish environments. Analysis of 35 crab samples identified 282 MPs, predominantly fragments, followed by fibers and pellets. The Pollution Hazard Index (PHI) was 658.46 (Level IV), indicating significant MPs pollution, while the coefficient of MPs impact (CMPI) showed that fragments posed the highest risk. These findings provide baseline data on MPs in Scylla spp., highlighting their role in MPs transfer and ecological risk assessment. This study emphasizes the need for continued monitoring and mitigation to address MPs pollution in aquatic environments.